Evaluation of the Effect of Piloted Implementation of Diversion Measures in Serbia - Džamonja Ignjatović, Tamara (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
During the last five years, a number of activities have been undertaken in order to improve the juvenile justice system in Serbia. They were intended to change the legislation and to set the stage for the implementation of planned legal solutions. The documents on standards and procedures for the application of correctional orders were developed, followed by piloting their implementation. The paper presents the results of an evaluation study conducted in four cities in Serbia: Belgrade, Novi Sad, Nis and Kragujevac. The evaluation assessed the quality of corrective orders, which were based on the clients’ satisfaction with various aspects of their implementation. The evaluation also assessed the outcomes of correctional orders based on changes in adolescents’ behaviour. Both aspects were evaluated from the perspective of all participants: children, their parents and the service provider, such as case managers and professionals responsible for the implementation of the order in the respective organisation. All five correction orders that were piloted were also evaluated. The sample included 90 young people aged 14 to 18 years (M = 16.03), 78 (80%) males and 12 (20%) females. The assessment was conducted as a test-retest study. Questionnaires developed specifically for the purposes of this evaluation were administered, as well as the Strengths and Difficulties Questionnaire – SDQ for the self-assessment of the adolescents. The results showed positive changes in young people after completing the correctional orders, which were primarily reflected in stopping antisocial behaviour, in improvement of their ability to predict consequences of their behaviour and in increased responsibilities towards commitments. Academic achievement and relationships with pro-social peers improved, as well as adolescents’ mood, whereas the degree of anxiety and tension decreased. Relationships and family communication improved; parents were actively involved in the care and supervision of their children, and they spent more time together and talked more. All respondents expressed satisfaction with the content of diversion measures and procedures, which they considered useful for their children and families. It can be concluded that the initial evaluation results of the application of corrective orders are encouraging in terms of social integration and prevention of relapse of youth in conflict with the law.